A prospective study on the diagnosis of peripheral lung cancer using endobronchial ultrasonography with a guide sheath and computed tomography-guided transthoracic needle aspiration. (19th January 2018) - Zhu, Jun; Tang, Feng; Gu, Ye
Background: It is difficult to collect peripheral lung cancer samples. This study analyzed the applicability of endobronchial ultrasonography with a guide sheath (EBUS-GS) and computed tomography-guided transthoracic needle aspiration (CT-TTNA) for the diagnosis of peripheral lung cancer. Methods: A prospective analysis of peripheral lung cancer patients was performed. The study included 150 cases in the EBUS-GS group and 177 cases in the CT-TTNA group. The diagnostic rate, pathological type, genetic status and complications were analyzed. Results: The diagnosis rates were 64.0% and 97.7% in the EBUS-GS and CT-TTNA groups, respectively. The EBUS-GS group had undergone the most operations of the upper lobes of both lungs, while there was no significant difference in the operation distribution among the lobes in the CT-TTNA group. Adenocarcinoma (64 cases versus 51 cases) was most commonly observed in both groups, followed by squamous cell carcinoma. The detection rates of patients who were given a genetic test were 96.1% and 98.9% in the EBUS-GS and CT-TTNA groups, respectively. The incidence of complications in the EBUS-GS group was significantly less than that in the CT-TTNA group. Conclusions: EBUS-GS and CT-TTNA both had operational limitations. The diagnostic rate of EBUS-GS was lower than that of CT-TTNA, but there were fewer complications. CT-TTNA had better tolerance. According to the specific location of the lesion, we recommend EBUS-GS for lesions with a diameter ⩽30 mm and CT-TTNA for lesions with a diameter >30 mm. CT-TTNA specimens were advantageous for genetic testing.